Weather-rice-nutrient integrated decision support system (WeRise) in Madagascar - CGIAR Research Program on Rice (2019)
Applicability of downscaled seasonal climate predictions was confirmed and on-farm trials for validation were set up for 2 sites in the central highlands of Madagascar.